Kierkegaard e a reabilitação do eu : um diálogo com o homem contemporâneo, sua natureza e cultura - Samuel, Fabian Sichonany (2023)
In general, this dissertation intends to be a dialogue between Existential Philosophy and contemporary man, the latter equipped with a religious nature that has been rejected by the culture that surrounds him. Currently, there is a demand for the rehabilitation of the self, lost and entangled by immanentist social forces that deny, in a compelling or subtle way, its spiritual possibilities. Facing such unfavorable context, Kierkegaard's Philosophy can offer a sense of rehabilitation of the fragmented self by indicating an adequate use of existence. The dissertation, being a dialogue between cultural demand and the intended philosophical response, is divided into two main parts. In the first part, we intend to achieve two primary objectives: in Chapter 1, from the analysis of the religious phenomenon, as well as from the understanding of the insufficiency of its approach by the sociological method, which comprehends it only superficially, both supported by the idea of complexity, we enter into a psychological terrain, with the purpose of exploring this phenomenon in depth from human innerness. We conclude that man is equipped with an unconscious and structural religious nature. In Chapter 2, we seek to analyze how this religious man relates to his culture. We understand that the greater meaning of existence, or supersense in Viktor Frankl's considerations, has been rejected in two main ways. In the first, there is a blunt rejection to the idea of God and of religions in general, materialized in a strong criticism. In the second, we perceive a very sophisticated and singular subtlety, since there is no blunt criticism of the idea of God, but a diffuse invitation throughout culture to an immanent, hedonistic, and presentist way of life without transcendent referents. This cultural spirit has turned man away from himself and has made him inauthentic and incomplete from the point of view of the self. Faced with this reality described in the first part of the work, we establish a dialogue with Kierkegaard, since in his Philosophy we find elements capable of responding to this contemporary demand for subjectivity. The answer lies in the existential process of rehabilitation of the self, which is anchored in three basic conditions. The first condition is in Chapter 3 and is based on the use of despair, present in contemporary man, as a way of giving him the awareness that he possesses an eternal and underused part of the self, and therefore cannot authentically live his existence. Thus, despair can be understood as a means for the individual to become aware that underused potentialities benefit him, in a kind of self-knowledge. There is also a second condition in this existential path of rehabilitation, presented in Chapter 4, which refers to the use of existential anxiety as a way to make the individual aware of his own freedom. In addition, anxiety, insofar as it impels man to travel the paths of existence, makes him capable of overcoming and even transgressing the cultural context that surrounds him, especially when it is unfavorable in terms of spirituality, as is the case with contemporary scenario. Finally, we describe the third and last condition for the self to become accomplished; it is based on the concepts of instant and faith. The individual must give up the fleeting moments of life, even dispensing the Socratic occasion – when the master was able to produce the knowledge inherent in subjectivity – to surrender to the instant filled by eternity. At this moment, there is an encounter with the previously hidden divine purposes, a contact with the absolute, an this leads to a radical transformation of the self. Both the knight of faith and the contemporary disciple are the characters who best represent the term of this rehabilitation process, its point of arrival. These characters are, therefore, examples of integrity and authenticity of the self, and tell us about the spiritual opening so necessary for the contemporary man.